Collection of Short Stories Lukisan Untuk Papa: Reflective Sociological Analysis Class and Social Affairs Through Short Stories Focusing on Titled Stories Aku Ingin Pulang - Viki Savira Nasyarin; Nurholis Nurholis (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This article tries to analyze the class or social conflict reflected through one of the short story titles, especially the one entitled Aku Ingin Pulang from the short story collection Lukisan Untuk Papa by Nanan Ginanjar. Through descriptive qualitative analysis by critically reading literary works which will then be identified. The depiction contained in the literary work is not only a narrative plot, but also a reflection of the social, cultural and political conditions prevailing in Indonesian society through a series of words that the author tries to describe through his writing. There are sixteen short story titles contained in this short story collection book which of course contains various types of social life including conflicts that generally occur in the surrounding community such as conflicts between families, economic conflicts, and cross-generational conflicts. However, this discussion only focuses on the short story entitled “Aku Ingin Pulang”. The results of the study: (1) Ari as the main character who misses his life in the village. (2) Ari's father's efforts to improve the family's economy by betting his fate in the capital have reached a deadlock. (3) The existence of several lower middle class families living under the flyover is a real picture that occurs around the village.